SEJARAH DAN PERKEMBANGAN GEREJA KRISTEN PROTESTAN SIMALUNGUN RAYA USANG KECAMATAN DOLOG MASAGAL KABUPATEN SIMALUNGUN 1903-2023 - Ayu Lestari Sidauruk; Andres M. Ginting; Satria Chandra Chandra (Jurnal Pendidikan Sejarah Humaniora dan Ilmu Sosial, 2026)
Based on the background of the establishment of the GKPS Raya Usang church, this church is one of the oldest churches in the GKPS congregation. The purpose of this study is to explain historically how the history and development of the GKPS church in Raya Usang. The method used by researchers in this writing is the Historical method. The results of the study show that the formation of the congregation and the establishment of the GKPS Raya Usang which is part of the Raya Usang Resort in Dolog Masagal District cannot be separated from the struggle carried out by the missionary August Theis and the evangelists along with all the figures who played a role in the establishment of this church including the spirit and unity of the village community of Raya Usang, by having the awareness to build a church building that should be separated from the school building. In its development, the GKPS Raya Usang church cannot be separated from the influence of the leadership of the congregation council who plays an active role in carrying out its duties and responsibilities through the "Tri-task of the Church's calling" in growing and developing the faith of the members of the GKPS Raya Usang congregation. The development of the GKPS Church in Raya Usang has resulted in the growth of congregation members every year, the change in the name of the church from HKBP to HKBPS and in 1963 to GKPS. The missionary school educational institution equivalent to elementary school was also established as a work of the Protestant Christian Church in Raya Usang, although this school no longer exists because an elementary school was established in the presidential instruction era since the independence era.